Microbiota y aspectos inmunológicos relacionados con el tratamiento con terapia dirigida en pacientes con melanoma irresecable o metastásico. - Guardamagna, Mora (UMA Editorial, 2025)
Metastatic melanoma, the deadliest form of skin cancer, has seen a rise in both incidence and prevalence. Despite recent advances in treatment, resistance to therapies remain a significant challenge, driving the need for reliable prognostic and predictive biomarkers to enhance therapeutic outcomes. In this context, gut microbiota (GM) and genes involved in immune activation emerge as promising biomarkers. GM has been associated with carcinogenesis, immune modulation, and treatment responses. While it has been extensively studied as a prognostic and predictive biomarker in immunotherapy-treated melanoma, no evidence has been published studying its role in patients treated with BRAF/MEK inhibitors. This prospective, observational study aimed to evaluate the prognostic and predictive value of GM and immune-related genes in response to BRAF/MEK inhibitors, as well as the impact of GM on the occurrence of treatment related adverse events (TRAE). Blood and fecal samples were collected at baseline and three months after treatment initiation from 26 patients with unresectable or metastatic melanoma, recruited between March 2019 and November 2022. Out of these, 24 patients were included in gene expression analysis, and 20 were analyzed for GM composition. The GM cohort was stratified based on the presence of complete response (CR) to targeted therapy and appearance of moderate-to-severe toxicity. Gene-expression analysis was further stratified according to presence of objective response (ORR), which included CR and partial response, as well as the presence of CR alone. GM analysis found no differences in alpha nor beta diversity among subgroups. However, baseline LEfSe analysis found an enrichment of Firmicutes - family Lachnospiraceae and genus Adlercreutzia - and Actinobacteria - family Coriobacteriaceae - in CR. An abundance of Proteobacteria - families Pasteurellaceae and Firmicutes - and Clostridium, were observed in No-CR.
Keywords: Melanoma - Aspectos inmunológicos - Tesis doctorales; Flora intestinal; Melanoma metastásico; Microbiota; Terapia dirigida; Sistema inmune; Vía BRAF